Kritik af kritikken: Den danske hvidhedsdebat anskuet igennem tre kritiske paradigmer - Gade, Solveig; Schultz, Laura Luise (Peripeti, 2016)
The article traces recent debates and conflicts in Danish literary and theatre criticism. These developments and discussions are analysed as manifestations of three different paradigms of critical approach defined by Gavin Butt, Irit Rogoff, and Eve Kosofsky Sedgwick, among others: 1) A classic Kantian model of the allegedly objective, universal judgment that Irit Rogoff calls criticism; 2) a deconstructive, ‘paranoid’ reading for the implicit hierarchies in a work that Rogoff calls critique; 3) a performative, reparative and bodily invested approach that Rogoff calls criticality. The article explores how these different paradigms are simultaneously activated in different constellations in recent heated debates on the importance of race, gender and sexual orientation in contemporary art and literature, and in the critical reception of these.